Evidence Of Endophytic Diazotrophs Migration From Root To Leaf Tissues Of Oil Palm Using Paddy As A Plant Model - Khairuddin, Dzulaikha (2012)
Endophytic diazotrophs are bacteria that occupy the microniches in plant tissues. In this case, they are able to fix nitrogen and provide N source to the plant with less environmental constraints. Research was conducted to isolate and identify endophytic diazotrophs from oil palm leaf tissues. The isolates were then tagged with gfp gene to track their colonization inside rice plant tissues. The isolates were identified as nitrogen fixers based on the results of the Acetylene Reduction Assay (ARA) and successful PCR amplification of the nifH gene. The potential of isolates to produce indole-3-acetic acid was also estimated by Salkowski’s colorimetric test. Identification was performed using 16S ribosomal DNA (rDNA) sequence analysis as well as phenotypic characteristics of the isolates on Red Congo agar, Nfb solid and semi solid malate media and under light microscope were also observed. Nine bacterial strains of endophytic diazotrophs were successfully isolated from oil palm leaf tissues. Based on molecular and phenotypic characterizations, the endophytic diazotrophs were phylogenetically close to genera Azospirillum sp., Acinetobacter sp., Acetobacter sp., Enterobacter sp. and Phytobacter sp. To study the colonization pattern, the bacteria Enterobacter sp. strain USML2, was transformed with pGFPCR vector to tag it with gfp gene. The tagged Enterobacter sp. strain USML2 was introduced to the root system of rice plant. After coming into contact with the rice plant root system the bacteria showed an unusual spreading to other plant part where in 24 hours after inoculation, 3.44x106 CFUgram- (fresh weight) of gfp-tagged Enterobacter sp. USML2 were observed in root section. While 3.21x104 CFUgram- (fresh weight) of gfp-tagged Enterobacter sp. USML2 found in stem section and 3.44x104 CFUgram- (fresh weight) of gfp-tagged Enterobacter sp. USML2 found in upper stem section. With 5.31x104 CFUgram- (fresh weight) of gfp-tagged Enterobacter sp. USML2 found in leaf tissues, it is concluded that bacteria migration happens from roots to leaf of rice plant. Dense colonization was observed on the primary and secondary roots and also on the junction of emergence of the lateral roots and subsequently to stem and leaf tissues. Results showed that the colonization pattern of Enterobacter sp. strain USML2 was similar to that of other endophytic bacteria isolated from non-legumes. Enterobacter sp. strain USML2 reached entry inside the root at the sites of emergence of lateral roots, without formation of infection threads as in the case of symbiotic rhizobacteria.